Head and neck squamous cell cancer – the role of computed tomography enhanced with perfusion imaging in tumour staging - Trojanowska, Agnieszka; Trojanowski, Piotr; Drop, Andrzej; Klatka, Janusz (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study: To determine the added value of computed tomography perfusion (CTP) images combined with contrast-enhanced computed tomography (CECT) images in staging of head and neck squamous cell cancer (SCC). Material and methods: Forty-seven consecutive patients with histologically proven squamous cell cancer of the head and neck and qualified for surgical treatment were prospectively evaluated in 2 groups: based on CECT multiplanar reformations (axial, coronal and sagittal), and separately, based on CTP images combined with CECT data. Tumour stage was assessed in each group separately, with special emphasis on T4 stage, and results were compared with histological findings. Five patients underwent endoscopic laser tumour resection, 11 underwent other tumour resection (glossectomy, pharyngectomy) and 31 patients underwent en-bloc resection of the hypopharynx and larynx, allowing detailed pathological evaluation of possible tumour infiltration into surrounding structures. Two experienced head and neck radiologists evaluated the images. Inter-observer agreement was tested with the modified k test. The χ 2 test was applied to compare the number of correctly staged tumours for the two methods and readers. Results : Inter-observer agreement was high (k = 0.88-0.90). Significant differences between the two groups were observed; with added CTP assessment more anatomical structures were rated positive for tumour infiltration and diagnostic accuracy of this method was significantly higher when compared to CECT images. Sole evaluation of CECT images in less advanced cases led to overestimation of the disease, since inflammation and slight oedema could not be differentiated from tumour. Conclusions : Contrast-enhanced computed tomography multi-planar images enhanced with CTP images were proven to improve accuracy in head and neck cancer staging. The added value of CTP may help to avoid overestimation of the malignant process and at the same time may facilitate depiction all infiltrated structures.